PROGRAM PONDOK RAMADHAN, UPAYA PENINGKATKAN KESADARAN DAN KEPATUHAN PUASA SISWA SMK YP 17 JOMBANG - Muhammad Syarofi (Universitas Bina Taruna Gorontalo, 2024)
The Ramadhan Pondok Program at SMK YP 17 Jombang aims to increase students' awareness and compliance in observing the Ramadan fast through structured education and ongoing supervision. The implementation of this program is expected to bridge the gap between social learning theory and religious practice, as well as increase religious values ​​among students. The service was carried out using the Participatory Action Research (PAR) method, which was used to implement the Pondok Ramadhan Program at SMK YP 17 Jombang. Through observation, discussion, action plans and participatory evaluation, this program aims to increase students' awareness and compliance with fasting by involving all stakeholders. The results of the Pondok Ramadhan Program service activities at SMK YP 17 Jombang show a significant increase in students' awareness and compliance with fasting as a form of program success, with increased student understanding and support from the school environment. To increase effectiveness in the future, it is recommended to add health education materials, practical activities, and involve parents more actively. The novelty of this program lies in the application of a structured and participatory approach in religious education, as well as in-depth evaluation which provides a basis for the development of religious programs in the future.